PERSPEKTIF HUKUM EFEKTIVITAS JAMINAN KESEHATAN MASYARAKATSEBAGAI WUJUD KEBERHASILAN PEMERINTAH DAERAH DALAM MEMENUHI PROGRAM STRATEGIS NASIONAL - Adilla Riski; Fadilla Salbilla; Margaretha BR. Sitanggang; Muhammad Khalid Kahn (CV. Multi Kreasi Media, 2022)
The existence of health insurance for the community is one form of the existence of the Regional Government in fulfilling national strategic programs. The effectiveness of the sustainability of this health insurance can be a measure of the success of local governments in carrying out their duties. Therefore, there is a need for a study through a legal perspective in assessing the effectiveness of Health Insurance on the sustainability of the national strategic program run by the Regional Government. The purpose of this study is to examine and assess the effectiveness of the sustainability of the Health Insurance implemented by the Regional Government in fulfilling the national strategic program. This research is a normative research method with a statutory approach and sampling using library materials. Therefore, this research is expected to be able to contribute ideas for law enforcement efforts in order to create a conducive atmosphere of community life and government.